A novel evaluation method for energy efficiency of process industry — A case study of typical iron and steel manufacturing process. (15th October 2021) - Na, Hongming; Sun, Jingchao; Qiu, Ziyang; He, Jianfei; Yuan, Yuxing; Yan, Tianyi; Du, Tao
Abstract: Energy efficiency is an extremely important indicator for exploring energy conservation and consumption reduction. The traditional energy efficiency assessment methods for process industry lack an in-depth thinking on energy utilization of the whole system. Based on the proposed required energy, this paper established an energy efficiency assessment method for process industry. By establishing material and energy flow networks, energy efficiency of typical iron and steel manufacturing process (ISMP) is analyzed and its influencing factors are discussed. The results found that the required energy of coking, sintering, pelletizing, blast furnace iron-making, basic oxygen furnace steel-making and steel rolling are 2626.2 MJ/t-coke, 1122.9 MJ/t-sinter, 992.3 MJ/t-pellet, 9781.5 MJ/t-hot metal, 393.95 MJ/t-molten steel and 445.3 MJ/t-steel products, respectively. The energy efficiency of typical ISMP is 66.9%. The energy efficiency of the ISMP can be effectively improved by adjusting the steel ratio, recovering waste heat and residual energy, and developing interface technologies. Highlights: Energy efficiency assessment method of process industry is proposed and established. The material and energy flow networks of iron and steel manufacturing process are established. The required energy of iron and steel manufacturing process is analyzed and given. Energy efficiency of typical iron and steel manufacturing process is evaluated and given. The influencing factor of energy efficiency is discussed.